1998
DOI: 10.1016/s0370-2693(98)00141-5
|View full text |Cite
|
Sign up to set email alerts
|

Conifolds from D-branes

Abstract: In this note we study the resolution of conifold singularity by D-branes by considering compactification of D-branes on C 3 /(Z 2 × Z 2 ). The resulting vacuum moduli space of D-branes is a toric variety which turns out to be a resolved conifold, that is a nodal variety in C 4 . This has the implication that all the corresponding phases of Type-II string theory are geometrical and are accessible to the D-branes, since they are related by flops.In the aftermath of the second superstring revolution the role of D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Hence, the fields that are dynamical are given by the set [p 1 , p 2 , p 3 , p 6 ] while the rest acquire non-zero vev and hence are resolved, and in this case the reduced charge matrix is obtained from (20) to be…”
Section: D-branes On Cmentioning
confidence: 99%
“…Hence, the fields that are dynamical are given by the set [p 1 , p 2 , p 3 , p 6 ] while the rest acquire non-zero vev and hence are resolved, and in this case the reduced charge matrix is obtained from (20) to be…”
Section: D-branes On Cmentioning
confidence: 99%
“…D-branes on the three-dimensional orbifold C 3 /(Z 2 × Z 2 ) have been studied in the absence of discrete torsion [9][10][11], and in its presence as well [4,5,12]. In the absence of discrete torsion, the moduli space of a D-brane on C 3 /(Z 2 × Z 2 ) is a blown down conifold.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of discrete torsion, the moduli space of a D-brane on C 3 /(Z 2 × Z 2 ) is a blown down conifold. Adding Fayet-Iliopoulos terms in 2 the gauge theory corresponds to partial [11] or complete [9,10] resolution of the singularity, depending on the non-vanishing combinations of the Fayet-Iliopoulos parameters. However, the scenario is rather different in the presence of discrete torsion [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Abelian orbifolds (Γ = Z n , Z n × Z n ) were investigated in [3,4,5,6]. The phase structure of the Kahler muduli space is investigated and it is shown that only geometric phases appear by using toric methods.…”
Section: Introductionmentioning
confidence: 99%